2020
DOI: 10.1016/j.jeurceramsoc.2020.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric assessment of fatigue damage in a SiCf/SiC ceramic matrix composite via in situ X-ray computed tomography

Abstract: To enhance the understanding of matrix cracking and damage progression on the macroscopic scale, within a 0/90º fibre reinforced SiCf/SiC ceramic matrix composite (CMC), X-ray computed tomography (XCT) imaging and analysis have been performed in conjunction with a commercially available in-situ mechanical loading device.CMC test coupons were subjected to tensile cyclic loads and inspected using XCT without removal from the tensile loading device. Attempts to measure and quantify the resulting damage using volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A theory also exists, which is independent from any oxidation hypothesis, stating that the SiC fibre strength is intrinsically time dependent due to the slow crack growth of flaws in the fibres. The time-dependent stiffness degradation is something not strictly related to fatigue [ 19 ]. Even without load cycle accumulation, damage is observed in a form of stiffness degradation even for static loads with a dwell time.…”
Section: Introductionmentioning
confidence: 99%
“…A theory also exists, which is independent from any oxidation hypothesis, stating that the SiC fibre strength is intrinsically time dependent due to the slow crack growth of flaws in the fibres. The time-dependent stiffness degradation is something not strictly related to fatigue [ 19 ]. Even without load cycle accumulation, damage is observed in a form of stiffness degradation even for static loads with a dwell time.…”
Section: Introductionmentioning
confidence: 99%
“…XCT is a powerful tool, which can be used to investigate the microstructure of composite materials before and after the chemical vapor deposition process [29] or to qualitatively describe the corrosion of steel-fiber reinforced polymer bars [30]. Moreover, XCT can be used in the in situ observation of degradation processes, such as SiC f /SiC composite fatigue testing [31] or steel bar corrosion in cementitious matrix [32].…”
Section: Introductionmentioning
confidence: 99%
“…In situ studies allow damage evolution to be observed, and can support the use of image-based simulations to understand the effects of microstructure on crack initiation [34,35]. In situ X-CT has been used to characterize damage development within CMCs including Cf/C-SiC, SiCf/SiC and Cf/SiC under compressive [36], tensile [3,37], flexural [38] and fatigue loading [39]. Digital volume correlation (DVC) analysis, applied to in situ X-CT data, uses the inherent features of the microstructure to measure the 3D displacements and strains [40].…”
Section: Introductionmentioning
confidence: 99%